2016
DOI: 10.7863/ultra.16.01048
|View full text |Cite
|
Sign up to set email alerts
|

Hunger Games: Interactive Ultrasound Imaging for Learning Gastrointestinal Physiology

Abstract: Ultrasound is playing an increasingly important role in medical student education. Although most uses of ultrasound have focused on learning purely anatomic relationships or augmentation of the physical examination, there is little documentation of the value of ultrasound as a learning tool regarding physiology alone or in association with anatomy. We devised an interactive learning session for first-year medical students using ultrasound to combine both anatomic and physiologic principles as an integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Students in the SonoSlam national medical student US competition [16] and SonoGames resident competition [29] reported increased confidence and clinical performance. An US game to enhance learning of gastrointestinal anatomy and physiology for first-year medical students by measuring blood vessel velocity was successful in increasing student interaction [30]. This study, too, found that a game model is effective for material retention, at least in the short-term, increases student confidence in the material, and is positively received.…”
Section: Non-game Groupmentioning
confidence: 62%
“…Students in the SonoSlam national medical student US competition [16] and SonoGames resident competition [29] reported increased confidence and clinical performance. An US game to enhance learning of gastrointestinal anatomy and physiology for first-year medical students by measuring blood vessel velocity was successful in increasing student interaction [30]. This study, too, found that a game model is effective for material retention, at least in the short-term, increases student confidence in the material, and is positively received.…”
Section: Non-game Groupmentioning
confidence: 62%
“…Other educators have used the world of Harry Potter to highlight that, just like magic cannot fix every problem, medicine cannot cure every patient [8]. The use of contemporary literature as an educational tool is not limited to Harry Potter; others have used Star Wars to teach about psychopathology [9,10] or the Hunger Games to teach ultrasound to first-year medical students [11].…”
Section: Introductionmentioning
confidence: 99%